2020
DOI: 10.2147/ijn.s281649
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mitochondria-Targeting Oxygen-Sufficient Perfluorocarbon Nanoparticles for Imaging-Guided Tumor Phototherapy</p>

Abstract: Background Although photothermal therapy (PTT) and photodynamics therapy (PDT) have both made excellent progress in tumor therapy, the effectiveness of using PTT or PDT alone is dissatisfactory due to the limitations of the penetration depth in PTT and the hypoxic microenvironment of tumors for PDT. Combination phototherapy has currently become a burgeoning cancer treatment. Methods and Materials In this work, a mitochondria-targeting liquid perfluorocarbon (PFC)-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…In addition to the advantage for multimodal imaging, the NIR responsive PFC nanodroplets have also been designed to improve the therapeutic outcomes by combining PTT with photodynamic therapy, 8 , 21 chemotherapy, 13 , 16 or radiotherapy, 22 etc. It has been reported that the combination of PTT and other therapies can achieve better therapeutic outcomes compared to PTT alone.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the advantage for multimodal imaging, the NIR responsive PFC nanodroplets have also been designed to improve the therapeutic outcomes by combining PTT with photodynamic therapy, 8 , 21 chemotherapy, 13 , 16 or radiotherapy, 22 etc. It has been reported that the combination of PTT and other therapies can achieve better therapeutic outcomes compared to PTT alone.…”
Section: Introductionmentioning
confidence: 99%
“…The near-infrared responsive PFC nanodroplet usually has complex and delicate structures. 8–16 Nanosystems are typically fabricated using PFC as a core with a polymers/lipids shell, and PTT agents/drugs/genes embedded into the shell. 8–13 Alternatively, a hollow nanoparticle was prepared for PFC loading with conjugation/adsorption of PTT agents/drugs on its surface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations